4 Dec 2020: From science to policy and public health actions―Experience from the COVID-19 pandemic - Tanner, M. (International Livestock Research Institute, 2021)
Marcel Tanner, former director of the Swiss Tropical and Public Health Institute and professor and chair of epidemiology/public health and medical parasitology at the University of Basel, shares insights into the SARS-CoV-2 transmission/Covid-19 pandemic and the role of science in informing policy and public health actions. This video was recorded at ILRI on 4 December 2020. Find ILRI expertise and resources on zoonoses: ilri.org/zoonoses